A biological and ecological review of the endemic New Zealand genus Alseuosmia (toropapa; Alseuosmiaceae). Issue 1 (2nd January 2020) - Shepherd, Lara D.; de Lange, Peter J.; Townsend, Andrew; Perrie, Leon R.
ABSTRACT: We review the biology and ecology of the endemic New Zealand genus Alseuosmia A. Cunn. The taxonomy of the genus has a complicated history with considerable debate about both its relationship to other genera and the number of species recognised within it. Alseuosmia is now considered to belong to the small Southern Hemisphere family Alseuosmiaceae. Five species are currently accepted within Alseuosmia ( A. macrophylla A. Cunn, A. turneri R. O. Gardner, A. pusilla Colenso, A. quercifolia A. Cunn and A. banksii A. Cunn). However, A. banksii is extremely morphologically variable and some forms that do not fit in to the existing taxonomy may warrant recognition at the species level. Unusual features of the genus include rayless wood and the apparent mimicry by some Alseuosmia species of unrelated plants.